Clinical characteristics and outcomes in patients with diabetes mellitus affected by COVID-19: a retrospective cross-sectional study from a tertiary care center in Pakistan - Asma Ahmed; Salaar Ahmed; Manahil Tariq Malik; Maheen Zahid; Muhammad Abdullah; Shamila Ladak; Maliha Taufiq; Faiza Qureshi; Ayesha Ali; Shalni Golani; Kinza Jawed; Sajjan Raja; et al. (BMC Endocrine Disorders)
Abstract Background COVID-19, caused by SARS-CoV-2, emerged in December 2019 and quickly became a global public health concern. Diabetes, a major risk factor for severe COVID-19, affects 537 million people worldwide, with high prevalence in low- and middle-income countries like Pakistan. Studies show diabetes increases the risk of severe COVID-19 complications and mortality. However, there is limited data on COVID-19 outcomes in diabetic patients in Pakistan. This study aims to fill this gap and examine factors affecting outcomes in this population. Methods We conducted a retrospective cross-sectional study at The Aga Khan University Hospital, Karachi, encompassing 2,346 confirmed COVID-19 patients from February 26, 2020, to September 6, 2021. Data on diabetic status, following ADA guidelines and other clinical outcomes were collected from medical records and patient interviews. Statistical analysis was performed using SPSS V.25. Results A total of 1,342 patients were included, with 864 males (64.4%) and 478 females (35.6%). The mean age was 56.59 ± 15.55 years. SARS-CoV-2 infection was the primary diagnosis for 741 patients (55.2%), while 601 patients (44.8%) had it as a secondary diagnosis. Of the total, 348 patients (25.9%) had T2DM, 2 patients (0.15%) had T1DM, and 991 patients (73.8%) were non-diabetic. The mean duration of diabetes was 2.01 ± 1.32 years. Diabetic patients had a significantly shorter mean hospital stay (4.99 ± 4.46 days) compared to non-diabetic patients (6.79 ± 7.32 days) (p < 0.001). The overall discharge rate was 70.3%, with a mortality rate of 10.7%. T2DM was associated with lower in-hospital mortality (p < 0.001) but higher rates of ARDS (p < 0.001). There was no significant association between T2DM and the risk of pulmonary aspergillosis, pulmonary embolism, or septic shock. Higher financial class was associated with longer hospital stays and a greater likelihood of being discharged home (p < 0.001). Conclusion In conclusion, our study highlights the heightened susceptibility of COVID-19 patients with concurrent T1DM and T2DM to developing ARDS. Despite no significant association found between diabetes and adverse outcomes, the crucial role of tailored care for high-risk groups, particularly those with diabetes, cannot be overstated.